Polymeric solvent engineering for gram/liter scale production of a water-insoluble isoflavone derivative, (S)-equol - Lee, Pyung Gang; Lee, Sang Hyuk; Kim, Joonwon; Kim, Eun Jung; Choi, Kwon Young; Kim, Byung Gee (Applied Microbiology and Biotechnology, 2018)
A potent phytoestrogen, (S)-equol, is a promising isoflavone derivative drawing our great attention owing to its various biological and clinical benefits. Through selective activation of the estrogen receptor ERβ or androgen receptor, (S)-equol reduces menopausal symptoms, osteoporosis, skin aging, hair loss, and incidence of prostate or ovarian cancers without adverse effects. Traditional biosynthesis of (S)-equol exploited non-productive natural equol-producing anaerobic bacteria that mainly belong to Coriobacteriaceae isolated from human intestine. Recently, we developed a recombinant Escherichia coli strain which could convert daidzein into (S)-equol effectively under an aerobic condition. However, the yield was limited up to about the 200 mg/L level due to unknown reasons. In this study, we identified that the bottleneck of the limited production was the low solubility of isoflavone (i.e., 2.4 mg/L) in the reaction medium. In order to solve the solubility problem without harmful effect to the whole-cell catalyst, we applied commercial hydrophilic polymers (HPs) and a polar aprotic co-solvent in the reaction medium. Among the examined water-soluble polymers, polyvinylpyrrolidone (PVP)-40k was verified as the most promising supplement which increased daidzein solubility by 40 times and (S)-equol yield up to 1.22 g/L, the highest ever reported and the first g/L level biotransformation. Furthermore, PVP-40k was verified to significantly increase the solubilities of other water-insoluble natural polyphenols in aqueous solution. We suggest that addition of both HP and polar aprotic solvent in the reaction mixture is a powerful alternative to enhance production of polyphenolic chemicals rather than screening appropriate organic solvents for whole-cell catalysis of polyphenols.
Keywords: (S)-equol; Hydrophilic polymers; Polyphenols; Solvent engineering; Whole cell; Equol; Escherichia coli; Industrial Microbiology; Isoflavones; Solvents; Water; (S)-equol; Hydrophilic polymer; Polyphenol; Solvent engineering; Whole-cell catalysis